Chiral helimagnetism and stability of magnetic textures in MnNb3 S6 - Osorio, Santiago Antonio (2023)
We analyze the nature of the modulated magnetic states in a micromagnetic model for the monoaxial chiral magnet MnNb3S6, for which the Dzyaloshinskii-Moriya interaction and the dipolar interaction compete evenly. We show that the interplay between these interactions lead to a complex phase diagram including ferromagnetic states, fanlike states, in-plane stripes patterns, and chiral soliton lattices. In particular, stripe patterns and chiral soliton lattices comprise nontrivial topological states with fixed chirality. The obtained phase diagram exhibits a strong dependency on the thickness and on the strength of the Dzyaloshinskii-Moriya interaction. Our results can help to understand the magnetic properties of systems such as MnNb3S6.